Mengurangi Perilaku Menggigit Kuku Menggunakan Teknik Aversi bagi Anak Disabilitas Intelektual Ringan (Single Subject Research Kelas III di SLB Wacana Asih Padang) - Finda Afriyen; Johandri Taufan; Zulmiyetri Zulmiyetri; Yosa Yulia Nasri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study discusses reducing nail-biting behavior using aversion technique for children with mild intellectual disabilities in Class III at SLB Wacana Asih Padang. The purpose of this study is to see whether the aversion technique can reduce nail-biting behavior in children with mild intellectual disabilities at SLB Wacana Asih Padang. This research was applied using a Single Subject (SSR) design type A-B, with the research subjects being children with mild intellectual disabilities in Class III at SLB Wacana Asih Padang. The variable tested in this study is the aversion technique as the independent variable, while nail-biting behavior is the dependent variable. Data were collected through direct observation, and the results were analyzed using visual graphics. The research results proved that the nail-biting behavior of children with mild intellectual disabilities reduced when applying the aversion technique, as seen from the comparison of values between the baseline condition (A) and the condition when the method was applied (B). Thus, the researchers concluded that the aversion technique can reduce nail-biting behavior in children with mild intellectual disabilities. This study has limitations in the limited number of subjects and the relatively short duration of the intervention, so the results cannot yet be generalized widely. Therefore, it is recommended that future research involves more subjects, extends the intervention time, and combines the aversion technique with other approaches to achieve more optimal results.